Pengembangan Aplikasi Point of Sales Warung dan UMKM "WarunkQu" menggunakan Framework Flutter - Grinaldi Wisnu Tri Prasetyo; Fajar Pradana; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Nowadays, technological developments require various sectors to be able to develop their capabilities. One of the sectors that must follow the development of this technology is MSMEs as an important pillar in the Indonesian economy at a GDP of 61.07%. In its practice, only 9% of MSMEs have digitized, but another 30% have not implemented it and are still using conventional methods (manual) in their sales system. This manual method usually takes a long time and is not effective because it is prone to calculation errors that can hinder decision-making, such as errors in the inventory system and sales reports. Based on this problem, the researcher developed a point of sale application, namely WarunkQu, using the flutter framework to make it easier for MSME actors or shop owners to record and get sales reports. This research was conducted using the waterfall method because the problems obtained were clearly defined. This system uses the flutter framework to get output in the form of a mobile application that can be used on all android devices. The results of testing the WarunkQu application were carried out using functional testing (black box testing) with an average success rate of 100% and usability testing with an average value of 91. This value is included in the very good category and is assumed to be accepted by users.